Network Security : Attacks and Defence. - Mudgal, Sahil; Nayak, Pooja (IJRDO -Journal of Computer Science Engineering, 2015)
Network Security has become very important in today’s world, as a result of which various methods are adopted to prevent it. Network administrators need to keep up with the recent advancements in both the hardware and software fields to prevent their as well as the user’s data. This paper describes the various attack methods which are used, as well as various defence mechanism against them.